The Influence of Compensation and Work-Life Balance on Intention to Stay of Aramex Indonesia Employee - Dafrayu, Firly; Mohammad Amas Lahat, Mohammad Amas Lahat (Research of Economics and Business, 2024)
Intention to stay in an organization is influenced by various factors, one of which is flexibility in working hour arrangements that can improve work-life balance, productivity, engagement, and organizational attractiveness for potential talents. This study aims to explain the effect of compensation and work-life balance on employee intention to stay at Aramex Indonesia. This type of research is descriptive quantitative. The population in this study were all employees of Aramex Indonesia using non-probability sampling method saturated sampling technique. The results showed that the multiple regression model equation. Managerial Implications The findings of this study reveal that compensation and work-life balance significantly influence the intention to stay among Aramex Indonesia employees. These insights suggest that management should prioritize competitive compensation packages and policies that support work-life balance to retain talent. Offering flexible working arrangements and ensuring that employees feel adequately rewarded for their contributions can enhance job satisfaction and loyalty, thereby reducing turnover rates. Implementing these strategies can help Aramex Indonesia maintain a stable and motivated workforce, ultimately contributing to the company's long-term success and operational efficiency.